Cooperative Reductive Elimination: The Missing Piece in the Oxidative‐Coupling Mechanistic Puzzle. Issue 8 (25th January 2016) - Funes‐Ardoiz, Ignacio; Maseras, Feliu
Abstract: The reaction between benzoic acid and methylphenylacetylene to form an isocoumarin is catalyzed by Cp*Rh(OAc)2 in the presence of Cu(OAc)2 (H2 O) as an oxidant and a leading example of oxidative‐coupling reactions. Its mechanism was elucidated by DFT calculations with the B97D functional. The conventional mechanism, with separate reductive‐elimination and reoxidation steps, was found to yield a naphthalene derivative as the major product by CO2 extrusion, contradicting experimental observations. The experimental result was reproduced by an alternative mechanism with a lower barrier: In this case, the copper acetate oxidant plays a key role in the reductive‐elimination step, which takes place through a transition state containing both rhodium and copper centers. This cooperative reductive‐elimination step would not be accessible with a generic oxidant, which, again, is in agreement with available experimental data. Abstract : Joint effort : The reaction between benzoic acid and methylphenylacetylene to form an isocoumarin is catalyzed by Cp*Rh(OAc)2 in the presence of Cu(OAc)2 (H2 O) as the oxidant. Its mechanism was elucidated by DFT calculations with the B97D functional, which showed that the overall transformation proceeds by cooperative reductive elimination with a transition state containing both rhodium and copper centers.